Uji Sensitifitas Candida albicans, Staphylococcus aureus, dan Fusarium Sp. Terhadap Myrmecodia sp., Jack Sebagai Faktor Pemicu Resiko Infeksi Pelvic Inflammantory Disease Secara In Vitro - Hujjatusnaini, Noor; Nirmalasari, Ridha; Amin, Astuti Muh; Mila, Mila; Sasmita, Sasmita; Ihsan, Afifi Raima; Karlina, Siti; Ajiza, Pratisa Defiera (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Myrmecodia sp., also known as ant plant, has therapeutic potential such as anticancer, antioxidant, anti-inflammatory, and other metabolic syndrome therapies, but there are still few publications on it. Candida albicans and Staphylococcus aureus are normal flora in the digestive and vaginal tracts, but under certain conditions, they can cause infections if their growth becomes excessive and is in an inappropriate location. Conversely, although Fusarium sp. is not part of the normal flora, these three microflora can be triggering factors for pelvic inflammatory disease infections in other organisms. The study aims to determine the sensitivity comparison of Candida albicans, Staphylococcus aureus, and Fusarium sp. to Myrmecodia sp., Jack in vitro. The research results obtained a significance value of 0.0000.05, where the most effective concentrations were Candida albicans at 3.2%, Staphylococcus aureus at 1.6%, and Fusarium sp. at 0.8% as triggering factors for pelvic inflammatory disease infections. The data show that Myrmecodia sp. extract effectively suppresses pelvic inflammatory disease infections caused by Candida albicans, Staphylococcus aureus, and Fusarium sp, with Fusarium sp. being declared to have a stronger sensitivity to Myrmecodia sp. extract.